2022
DOI: 10.1007/s41999-022-00656-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a modified Otago exercise program delivered through outpatient physical therapy to community-dwelling older adult fallers in Greece during the COVID-19 pandemic: a controlled, randomized, multicenter trial

Abstract: Key Summary Points Aim To investigate the effectiveness of a video-supported OTAGO exercise program (OEP) in balance, functional ability, fear of falls and number of falls in Greek older adults with a history of falls. Findings A 6-month OEP helped older adults to improve their balance and functional ability test scores as well as reduce fear and number of falls, both after the intervention and at the 12-month follow-up. However, the adherence to the progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
0
8
0
2
Order By: Relevance
“…[6] The reduced postural control ability could induce increased fall rates making elders more susceptible to cause injuries and long-term disabilities. [3] Additionally, the COVID-19 pandemic further exacerbated the social isolation of the elderly, decreasing their likelihood of engaging in physical activity and maintaining motor function, [7] which is especially serious for those living in NHs.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The reduced postural control ability could induce increased fall rates making elders more susceptible to cause injuries and long-term disabilities. [3] Additionally, the COVID-19 pandemic further exacerbated the social isolation of the elderly, decreasing their likelihood of engaging in physical activity and maintaining motor function, [7] which is especially serious for those living in NHs.…”
Section: Introductionmentioning
confidence: 99%
“…Main causative factors of falls are the deficits in strength and balance of older adults because aging affects muscles, bones, joints, and the nervous system [4] . Exercise has been shown to help reduce these deficits by protecting older adults from experiencing another fall [2,5,6] . Studies have shown that older adults participating in therapeutic exercise programs that include exercises such as balance and resistance training can have reduced fall risk by improving standing and walking performance [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Various methods of training older adults have been applied in the past for this purpose. The Otago exercise program [6,8] , Pilates [9] , and conventional resistance and balance programs have been shown to have a positive effect on reducing falls in older adults [10,11] . However, in recent years, special software games (exergames) have been developed that combine active physical participation with a friendly fun environment.…”
Section: Introductionmentioning
confidence: 99%
“…6 The percentage of Australians over the age of 65 is projected to increase from 13% (3 million people) in 2010 to around 24% (9 million people) by 2050 [6] . Physiotherapy can play a key role in preventing falls in older adults [6][7][8][9][10] . Many of the functions of the human body that are affected due to aging can be improved through physiotherapy interventions, especially through the implementation of therapeutic exercise programs [6,7] .…”
Section: Introductionmentioning
confidence: 99%